Constraints in Ginger Cultivation by Farmers of West Garo Hills District of Meghalaya - Sharma, Vicky; Longkumer, J.; Mary, N. O.; Sentinungshi; Das, Sanjoy (International Journal of Economic Plants, 2023)
A research was conducted in West-Garo Hills district of Meghalaya State, India during October 2020 to January 2021 so as to identify the major constraints involved in ginger cultivation as perceived by the respondents. Following the multi stage sampling method, two RD blocks i.e., Rongram and Daluwere purposively selected for the study with a total of 120 respondents from six villages. Descriptive research design was followed in this study. The study concluded that most of the ginger cultivators belonged to middle age category. The land holding under ginger cultivation was medium because of the hilly terrain. It was found that ginger cultivation had been a family tradition for generations thus promote large scale cultivation of ginger commercially. Ginger growers of the study area had average income. The farmers were getting very less return from ginger cultivation, therefore, to mitigate it, the Department of Agriculture, Government of Meghalaya initiated the transportation system called the 1917 i-TEAMS Ginger mission (Integrated Technology Enabled Agri- Management System) to facilitate remunerative price by eliminating the middleman. It was also found that farmers had interest towards new innovations and technologies and were willing to take high risk to get more income from ginger cultivation, therefore, concerned departments should build upon this interest in bringing about adoption of new practices. The major constraint was the lack of knowledge on pest and disease management, hence, the study recommended for training on plant protection measures.